Adsorption and transport behavior of arsenate on saline-alkali soils of tidal flat of Yellow Sea, Eastern China. Issue 1 (1st January 2019) - Luo, Ting; Sun, Jianxiong; Liu, Yang; Cui, Liqiang; Fu, Qiang
ABSTRACT: The adsorption of arsenic plays an important role in the mobility of this toxic element in the saline-alkali soil environment. The adsorption and transport of arsenate [As(V)] in saline-alkali soils were investigated in this study. The results of kinetic experiments indicated that the rate of As(V) adsorption was initially rapid and then became slow, which were modeled well with the pseudo-second-order rate model. The adsorption isotherms were best fitted by the Langmuir and Freundlich sorption equation. The maximum adsorption capacity of soil L1was the lowest (202.8 mg/kg), and that of soil D1 was the highest (686.6 mg/kg). The difference in adsorption capacity in five soils was mainly due to the CaCO3 content. The CaCO3 enhanced As(V) adsorption due to the adsorption and coprecipitation of calcium with As(V). The column experiments demonstrated that the transport of As(V) in soils was detained and the degree of detainment increased with decreasing As(V) concentration.